1968
DOI: 10.1111/j.1469-1809.1968.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited variations in human phosphohexose isomerase

Abstract: SUMMARY 1. The elctrophoretic pattern of phosphohexose isomerase has been examine in the blood of 3397 unrelated individuals from several different populations groups. 2. Eight variant phenotypes were identinfied and these were designated PHI 2‐1, 3‐1, 4‐1, 5‐11 6‐1, 7‐1, 8‐1, 9‐1. All of these were rare in the populations studied except the variant designated PHI 3‐1, which was observed with a frequency of about 1% in a mixed population of Asiatic Indians. 3. Studies of selected families indicated that the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
1

Year Published

1971
1971
1981
1981

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(60 citation statements)
references
References 15 publications
6
52
1
1
Order By: Relevance
“…For dehydrogenase enzymes, one half of the gel was stained for 6-PGD and G-6PD by the method of Fildes and Parr (1963) and the other half was stained for lactate dehydrogenase (LDH) and malate dehydrogenase (MDH) as described by Kirk et al (1971). Phosphohexose isomerase (PHI) was performed by the method of Detter et al (1968).…”
Section: Methodsmentioning
confidence: 99%
“…For dehydrogenase enzymes, one half of the gel was stained for 6-PGD and G-6PD by the method of Fildes and Parr (1963) and the other half was stained for lactate dehydrogenase (LDH) and malate dehydrogenase (MDH) as described by Kirk et al (1971). Phosphohexose isomerase (PHI) was performed by the method of Detter et al (1968).…”
Section: Methodsmentioning
confidence: 99%
“…Collection 4 ,umoles of glucose-6-P and 100 ,umoles of buffer in a total reaction volume of 1.0 ml. The formation of fructose-6-P was measured by the Roe method (14).…”
Section: Methodsmentioning
confidence: 99%
“…The quantity of the enzyme preparation added and the incubation time at 30 C were adjusted so that the final readings were between 0.2 and 0. 4 Figure 1 shows that the dialyzed homogenate from endosperms or embryos of developing seeds gives three peaks of GPI activity following chromatography on DEAE-cellulose. The activities from fractions 3 to 8, 10 to 14, and 17 to 24 are designated, respectively, as I, Ia, and II.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study four examples of the PHI 3-1 combination were detected, all the other persons being PHI 1-1. Detter et al (1968) first described PHI 3-1 phenotypes among Indians living in England, and Blake et al (1972) have also found just over 1% PHI 3-1 persons in a large series from north India. The finding of a similar frequency among Lebanese in the present study suggests that the PHP allele is widely distributed in the Middle East.…”
Section: Red Cell Enzyme Groupsmentioning
confidence: 98%